Neglected tropical diseases and socio-environmental vulnerabilities in Amazonian capitals (Research, Society and Development, 2020)
This study assesses the epidemiological situation of neglected tropical diseases (NTDs) with the highest occurrence in the Amazon and its association with socio-environmental vulnerabilities. An ecological, descriptive study was carried out in the period between 2007 and 2016 about notified NTDs, in addition to data on the Municipal Human Development Index (MHDI), basic sanitation and population growth in the capitals of the Legal Amazon. The data obtained were organized in Excel spreadsheets for the application of descriptive statistics, principal component analysis (PCA) and hierarchical cluster analysis (HCA). The diseases reported were dengue, tuberculosis, American cutaneous leishmaniasis, schistosomiasis, visceral leishmaniasis and Chagas disease. All capitals presented at least four NTDs. These data were confirmed through the PCA and HCA, which found that the NTDs identified could be grouped by similarities between the values. Most capitals have had high population growth and MHDI in recent years, however, sewage and water supply services fall short. The study showed that there is a association between the reported diseases and data on population growth and basic sanitation, which may show a geographical neglect. One way to change this epidemiological reality in the Amazon is to elaborate public policies, with financial planning directed to the realization of viable and effective projects that offer constant services of basic sanitation, drinking water and health education for this population.